PKM MAHASISWA UNIVERSITAS INDO GLOBAL MANDIRI SOSIALISASI PERENCANAAN USAHA KERIPIK KACA BUSINESS MODEL CANVAS - Muhammad Radjab Athalla; Muhammad Dzaironi; Lesi Hertati; Terttiaavini; Agustina Heryati; Asmawati (Transpublika Publisher, 2021)
The business world requires a business plan that can help entrepreneurs prepare everything needed for the smooth running of their business. This business planning can be made in the form of a business plan. One of the business plan models that has many advantages is the Business Model Canvas. The purpose of writing this article is to find out what needs to be considered to make business planning using Business Model Canvas. The results of the literature review show that by using the Business Model Canvas, business planning becomes clearer and more focused. The glass chips business which is an example in the application of the Business Model Canvas becomes more focused and clear. Therefore, in making a Business Model Canvas, there are 9 important components including Customer Segment, Value Propositions, Channel, Customer Relationship, Revenue Streams, Key Activities, Key Partnerships, Key Resources and Cost Structure that need to be considered and clearly arranged to help the business run smoothly.